Technologies of subsumption in capital - Oliva, Carlos (2023)
This article revisits Marx's theory of subsumption and elaborates its centrality for comprehending contemporary capitalism from a global perspective. It explores the forms of capitalist subumption, first in terms of Marx's classic notions of 'formal' and 'real' subsumption, in which social and technological mechanisms of domination unfold within capitalist production. It then seeks to broaden the scope of analysis towards the sphere of commodity circulation and mercantile exchange, with its monetary and credit mechanisms of subsumption. Finally, it sketches a global conceptualisation of subsumption at the level of the process of social reproduction.